Paradoxical Effect of Quercetin Antioxidant on Goat Sperm Parameters After Cryopreservation - Borges, M S'a; Born, J. L.B.; Conti, L. M.; Segabinazzi, L. G. [UNESP]; Nichi, M.; Kawai, G. K.V.; Leite, R. F.; Peixoto, K. C.; Dell'Aqua, J. A. [UNESP]; Papa, F. O. [UNESP]; Crespilho, A. M. (My University, 2020)
BACKGROUND: Some antioxidants have been used in semen extenders to reduce adverse effects caused by excessive reactive oxygen species (ROS) production. The study was carried out to assess the effect of quercetin (QC) antioxidant therapy on goat semen submitted to cryopreservation. OBJECTIVE: To evaluate the effect of quercetin incorporation in different phases of the cryopreservation process of goat spermatozoa. MATERIALS AND METHODS: Five ejaculates from each of four goats (n= 20) were collected and split into four groups: Control (G1), without QC; G2, 15 μM of QC added to semen before centrifugation; G3, 15 μM QC added to semen after centrifugation; G4, 15 μM QC added to semen before centrifugation and 15 μM of QC added to semen after centrifugation (total of 30 μM of QC); and cryopreserved. All semen samples were evaluated after thawing for sperm kinetics, plasma membrane integrity, and ROS levels. RESULTS: Although lower concentrations of ROS were associated with groups that received antioxidant supplementation (P=0.0213), linear and dose dependent (P<0.05) reductions of the total and progressive sperm motility, velocity and percentage of fast cells were related to the QC groups. Likewise, plasma membrane integrity was better preserved (P=0.0154) in the control group (35.5%) than in groups that received QC (G2=32.6%, G3=32.4% and G4=26.7%). CONCLUSION: Although quercetin was efficient at reducing the oxidative stress related to sperm cryopreservation, it exerted a deleterious dose-dependent effect on the kinetics and integrity of the frozen goat semen, contradicating its use in the tested concentrations.